Neoantigen‐based vaccines as a promising strategy in cancer immunotherapeutics. Issue 1 (23rd February 2021) - Koshy, Anita G.; Rosenblatt, Jacalyn; Avigan, David
Abstract: The development of cancer vaccines is based on the premise that tumor cells are potentially targetable by host immunity through the effective presentation of tumor‐associated antigens to reactive T‐cell populations. Vaccine efficacy may be limited by the functional properties of effector cells including the lack of high‐affinity T cells to target self‐antigens. In contrast, neoantigens arise from tumor‐specific mutational events that generate epitopes that are potentially seen as foreign by host immunity. As such, neoantigen‐targeted vaccination provides a high level of tumor specificity, promotes greater T‐cell effector function, and minimizes off‐target toxicities. Next‐generation sequencing and high‐throughput computational algorithms have allowed for the identification of neoantigens in solid tumor and hematologic malignancies. Vaccine generation involves the screening of potential epitopes based on HLA restriction and reactivity by the T‐cell repertoire. Early phase studies have demonstrated feasibility of vaccine production and resultant potent immunologic responses. The clinical impact of neoantigen vaccination and its incorporation into combinatorial immunotherapeutic strategies is currently being explored.